Galleria Mellonella as A Surrogate Model System to Study Pathogenicity of Salmonella Enterica Serovar Typhimurium Strain ST4/74 and Enterohaemorrhagic E. Coli (EHEC) O157:H7 - Abdalla Hamed; Emad Essa; Salah Mohamed (AlQalam Journal of Medical and Applied Sciences, 2025)
In this research, Galleria mellonella larvae served as an in vivo model to examine the virulence of two pathogenic bacteria, Salmonella Typhimurium and Escherichia coli, along with their quorum-sensing receptor mutants, qseC and qseE. The most widely used inoculation route for Galleria is intra-haemocoelic injection through the last left pro-leg (the route used in this study). To determine the optimum bacterial dose, a range of inocula was used (103,104, 105, 106, and 107 CFU/10 µl injection volume); these were injected using a Hamilton syringe (26-gauge, 10 µl capacity). For control purposes, 10 larvae were inoculated with only Phosphate Buffered Saline (PBS) buffer. Lethal dose (LD50) was a useful tool for differentiating between high and low pathogenicity, but not for intermediate pathogenicity. The larvae were subsequently incubated at 37°C in a dark environment, and the culture dilution that resulted in the mortality of 50% of the larvae (LD50) for each replicate was assessed after 24 hours. For each experiment, a minimum of 10 larvae (located in 100 mm Petri dishes) were used per strain to be tested. Likewise, melanization could function as a criterion for evaluating the pathogenicity of the isolates, but it is essential to correlate it with other factors. Throughout the experiment, individual larvae were consistently assessed for indications of melanization and viability by observing their reflexive responses to physical contact. Mortality rates and survival curves were useful tools for characterizing non-pathogenic and highly pathogenic isolates. The precise numbers of inoculated bacteria into the larvae were carried out by plating serial dilutions of the inoculum onto Luria agar. The findings are expressed in terms of percent survival and are derived from at least three independent experimental trials.